Perancangan Primer untuk Deteksi Kandungan Gen Cytochrome b Babi dengan Metode Polymerase Chain Reaction dan Aplikasinya pada Berbagai Produk Industri - Dianti Devi Astari; Sania Gustiani Dewi; Sinta Setyaningrum; Bevi Lidya (Jurnal Kimia Fullerene, 2021)
Types of meat from food products that circulating in the market can be detected by Polymerase Chain Reaction with the cytochrome b gene as a marker. The most important and characteristic component for the PCR reaction is the primer, which is an oligonucleotide that acts as an initiator in the PCR reaction. In this study, the primer designed was intended to amplify the pig cytochrome b gene. The design was carried out with the help of the Primer-BLAST application, and manually, three pairs of primers came from BLAST primers, and one pair of primers was designed manually. The primer that has been designed is tested on pork, beef, and food industry products, such as pork sausage, beef sausage, and chicken sausage. The results of PCR amplification were identified qualitatively using 1% Agarose Gel Electrophoresis and visualized using a UV transilluminator. The primer designed manually to produce the whole pig cytochrome b gene with a product size of 1140 bp has succeeded in amplifying the product and is specific because it only produces bands in pork samples, while in chicken and beef samples, it does not produce bands. The three pairs of primers suggested by Primer-BLAST could amplify the porcine cytochrome b gene with band sizes of 121 bp, 272 bp, and 262 bp, but they are not specified yet because it also can amplify the gene in beef and chicken samples. The manual primer design is the best primer and can be further used to detect foodstuffs contains pig genes by PCR.